2021
DOI: 10.1371/journal.pntd.0009196
|View full text |Cite
|
Sign up to set email alerts
|

2-aminobenzimidazoles for leishmaniasis: From initial hit discovery to in vivo profiling

Abstract: Leishmaniasis is a major infectious disease with hundreds of thousands of new cases and over 20,000 deaths each year. The current drugs to treat this life-threatening infection have several drawbacks such as toxicity and long treatment regimens. A library of 1.8 million compounds, from which the hits reported here are publicly available, was screened against Leishmania infantum as part of an optimization program; a compound was found with a 2-aminobenzimidazole functionality presenting moderate potency, low me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The embryo developmental malformations observed, such as the absence of hatching and bradycardia, are directly correlated with prenatal loss in rabbits [6]. These results corroborate with a recent study carried out in rodents for the same compound Ferreira et al [10], the authors observed mortality and distress in the mice that were submitted to efficacy tests, finally, the development of the compound was discontinued. Thus, the use of the zebrafish model could have predicted the acute toxicity of the compound within 4 days (96 h), and tests on rodents could be avoided.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The embryo developmental malformations observed, such as the absence of hatching and bradycardia, are directly correlated with prenatal loss in rabbits [6]. These results corroborate with a recent study carried out in rodents for the same compound Ferreira et al [10], the authors observed mortality and distress in the mice that were submitted to efficacy tests, finally, the development of the compound was discontinued. Thus, the use of the zebrafish model could have predicted the acute toxicity of the compound within 4 days (96 h), and tests on rodents could be avoided.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the use of the zebrafish model could have predicted the acute toxicity of the compound within 4 days (96 h), and tests on rodents could be avoided. On the other hand, the compounds Carbamazepine and Benzimidazole did not cause changes in the development of the embryos when exposed to concentrations between 6.25 and 100 µM, which demonstrates that the OECD 236 test [10] predicted the safety of these compounds that are currently used in the treatment of human diseases and were previously approved in all preclinical and clinical trials.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations